Developing a self-management intervention to manage hypermobility spectrum disorders (HSD) and hypermobile Ehlers-Danlos syndrome (hEDS): an analysis informed by behaviour change theory. Issue 18 (28th August 2022) - Bennett, Sarah E.; Walsh, Nicola; Moss, Tim; Palmer, Shea
Abstract: Purpose: Hypermobility Spectrum Disorders (HSD) and Hypermobile Ehlers-Danlos Syndrome (hEDS) are heritable connective tissue disorders associated with joint instability and pain, but with scant guidance for supporting patients. The aim was to determine recommendations for an HSD/hEDS self-management intervention. Materials and methods: Barriers to self-management were mapped onto the Theoretical Domains Framework (TDF) and Capability, Opportunity, Motivation-Behaviour (COM-B) model in a behavioural analysis. A modified Nominal Group Technique was used to prioritise behaviour change technique (BCT) interventions ( n  = 9 women). Results: Possible BCTs incorporated: Education: Incorporating self-help strategies, education to improve their knowledge of HSD/hEDS, and how to judge information about HSD/hEDS. Training: In activity pacing, assertiveness and communication skills, plus what to expect during pregnancy, when symptoms can worsen. Environmental restructuring and enablement: Support from occupational therapists to maintain independence at work and home. Modelled behaviour: That illustrates how other people with HSD/hEDS have coped with the psychosocial impact. Conclusions: This study is the first to apply theoretically-informed approaches to the management of HSD/hEDS. Participants indicated poor access to psychological support, occupational therapy and a lack of knowledge about HSD/hEDS. Future research should evaluate which intervention options would be most acceptable and feasible. Implications for rehabilitation: Patients with Hypermobility Spectrum Disorders or Hypermobile Ehlers-Danlos Syndrome can be active partners in the co-design of behaviour change interventions. Behaviour change interventions should target psychological support and patient education, particularly patient information. Additional behaviour change interventions included environmental restructuring and enablement; adaptations to participants' environment with input from occupational therapy. Participants were keen to suggest opportunities for behavioural modelling; positive fist-person modelling narratives, written by those with HSD/hEDS, which addressed how they coped with the psychosocial impact of their condition.